The Algerian Scientific Journal Platform (ASJP): Do quality and quantity go hand in hand? - Hachani, Samir (Septentrio Conference Series, 2023)
Open access has made great strides in the last 30 or so years it has existed. From a forum of militant researchers to an institutionally led movement, then a fully global movement, it has made the scholarly communication landscape a different ball game. The convergence of the Internet (which now covers 67.9% of the world's population, from a mere 0.4% in 1995) and the ever increasing pressure of the famous serial crisis has made its occurrence unavoidable. Although originating in the Global North, where financial, political and technical means are present, it is the Global South that stands to benefit most from this new way of accessing and sharing information. In this context, there have been numerous and very successful experiments geared towards allowing fair sharing of information, experiments led most of the time by the Global North. On the other hand, the Global South has also launched experiments and programs in both green and gold routes to open access. There seems to have been a preference for the latter, as local, regional and continental experiments have come to light. Algeria, a Low and Middle Income Country (LMIC) has been at the forefront of open access in the Global South in general, and in the African and Arab context more specifically, and has launched and participated in numerous experiments either locally or regionally. Locally, the Algerian Scientific Journal Platform (ASJP) – and its “ancestor” WebReview – is a Diamond Open Access Site, and is the latest of the programs launched by the Directorate-General for Scientific Research and Technological Development (DGSRTD), under the auspices of the Ministry of Higher Education and Scientific Research. In order to “Algerianize” the sector, the Ministry has launched a very ambitious program to increase the number of Algerian students being granted a PhD. Doctoral students, in order to defend their thesis, are now required to publish a number of articles and attend conferences. Most PhD students in the humanities are unable to publish in high impact journals, so the ASJP is the appropriate place for them to do so. This presentation will analyze the different steps undertaken by the DGSRTD to make this platform an acceptable outlet for PhD students, how this platform has evolved over time, how it deals with the different submissions, the different classes and classifications it is made up of. More specifically, we will focus on the way the platform deals with the ever increasing number of students who need to publish to be able to defend their thesis. At the end, we will come up with a framework to make the ASJP a more “scientific” and acceptable platform, more in line with a modern and systematic platform, and propose a ranking and classification system that promotes the quality and not the quantity of submissions.